Kappa-opioid receptor gene (OPRK1) variations associated with opioid abstinence behaviors among chronic heroin users - Greenwald, Mark K.; Demery, Catherine; Moses, Tabitha E. H.; Burmeister, Margit (Frontiers in Pharmacology, 2025)
IntroductionResearch suggests kappa-opioid receptors (KORs) modulate drug use and stress-related behaviors. While some findings indicate KORs could influence initial susceptibility to opioid use disorder (OUD), few studies have examined whether variations in the gene encoding the receptor (OPRK1) relate to clinically-relevant behavioral variation among current opioid users. This study examined whether OPRK1 polymorphisms predicted opioid-abstinence phenotypes in three separate but conceptually-linked aims: (1) retrospective self-report of number of lifetime heroin-quit attempts at screening, (2) prospective assessment of opioid-abstinence initiation during a two-week buprenorphine (8 mg/day sublingual) outpatient stabilization period, and (3) prospective assessment of opioid lapse during a three-week buprenorphine dose-tapering outpatient period (4-mg/day, 2-mg/day and 0-mg/day during weeks 1-3, respectively).MethodsOPRK1 genotype and opioid-abstinence phenotype data (urinalysis and self-report) were obtained from current regular heroin users. Genotype-phenotype analyses controlled for self-identified race and heroin-use duration.ResultsOPRK1 rs7817710 (intron) T/T homozygotes (n = 145) reported significantly more heroin-quit attempts than G/T heterozygotes (n = 86) or G/G-homozygotes (n = 35). During outpatient buprenorphine stabilization, OPRK1 rs6989250 (intron) C/C homozygotes (n = 43) provided a significantly lower proportion of opioid-free urine samples than G-allele carriers (n = 7). During buprenorphine dose tapering, OPRK1 rs3802281 (3’UTR) C-allele carriers (n = 21) and rs7817710 G-allele carriers (n = 11) lapsed to opioid use significantly more slowly than T/T homozygotes at either locus (n = 17 and n = 16, respectively). The rs3802281–rs7817710 haplotype block was associated with Experiment 1 binary phenotypes.ConclusionThese findings implicate OPRK1 genetic variation in several opioid-abstinence phenotypes. These results, if replicated, could improve understanding of the course and treatment of OUD.